A population-based data-linkage study of prescribed pain medications dispensed to persons with cerebral palsy - Guiomar Garcia Jalon; Aideen Maguire; Oliver Perra; Anna Gavin; Dermot O'Reilly; Allen Thurston (International Journal of Population Data Science, 2018)
Background Population-based surveys to investigate pain in cerebral palsy (CP) can be costly and results limited by recruitment bias, recall issues, and differences between self-reports and parental accounts. Secondary data analysis may provide a cost-effective alternative to study this issue and its impact in this population.